1988
DOI: 10.1113/jphysiol.1988.sp017285
|View full text |Cite
|
Sign up to set email alerts
|

Binocular co‐ordination of human vertical saccadic eye movements.

Abstract: SUMMARY1. The binocular co-ordination of human vertical saccades was analysed systematically over the full oculomotor range, with a precise and accurate scleral sensor coil technique. Effects of amplitude (1-25-70 deg), direction (upward vs. downward and centripetal vs. centrifugal), as well as position (upper or lower sector of vertical oculomotor range), were investigated systematically in three subjects.2. All saccades were made voluntarily between continuously presented pairs of targets, which subtended eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
110
3
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 3 publications
23
110
3
4
Order By: Relevance
“…We have observed from experimental recordings of ourselves and others (see for example Collewijn et al, 1988a;Collewijn et al, 1988b;Becker & Jfirgens, 1990;) that trajectories of saccades show a fair amount of variability. Present models predict a fixed trajectory between start and landing position of saccades.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We have observed from experimental recordings of ourselves and others (see for example Collewijn et al, 1988a;Collewijn et al, 1988b;Becker & Jfirgens, 1990;) that trajectories of saccades show a fair amount of variability. Present models predict a fixed trajectory between start and landing position of saccades.…”
Section: Introductionmentioning
confidence: 80%
“…A further extension of experimental data was obtained from accurate measurements of conjugate (Collewijn et al, 1988a;Collewijn et al, 1988b) and disjunctive (Erkelens et al, 1989) saccades in the two eyes together. The data showed that saccades are not as stereotyped as once has been thought.…”
Section: Introductionmentioning
confidence: 99%
“…Less detailed reports on nonconjugate adaptations have been issued before by the same authors (Collewijn, Erkelens & Steinman, 1988a), and also by Levi, Zee, Hain, Fletcher and Miller (1988), Schor, Gleason and Horner (1988), Horner, Gleason and Schor (1988), and by Zee and Levi (1989). Schor, Gleason and Horner (1990) recently published an extensive experimental study on short-term adaptation, while Oohira, Zee and Guyton (1991) recently studied nonconjugate adaptation in one case of long-standing anisometropic correction.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, we also note that the tendency to undershoot the target cannot be taken as evidence for incomplete integration of the contour shape, as this is a general and well-documented property of human eye movements [39,40]. As a side note, the differences observed in our dependent measures between horizontal and vertical saccades and between upward and downward saccades should also not be interpreted as direct evidence for anisotropies in the contour integration mechanism, as they are due at least in part and perhaps entirely to direction-dependent differences in saccades per se [52].…”
Section: Discussionmentioning
confidence: 69%